EFEKTIFITAS KINERJA DAN EFESIENSI PENGELOLAAN ANGGARAN PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) DENPASAR - Lestari Dewi, Ni Komang Ayu Tri; Agus Ariana, I Komang (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The State Assets and Auction Service Office (KPKNL) is a vertical agency of the Directorate General of State Assets (DJKN) within the Ministry of Finance of the Republic of Indonesia. The main task of the State Property and Auction Service Office (KPKNL) is to realize, secure, and improve the management of state assets, management of receivables, and auctions efficiently and effectively. Constant policy updates and the occurrence of a state budget deficit have caused the Denpasar KPKNL to be able to generate optimal state revenues. If the budget management planning does not run efficiently and does not have an effective revenue performance, it will result in delays in the smooth process of Non-Tax State Revenue (PNBP). The purpose of carrying out the activity is to examine the Performance Effectiveness and Efficiency of Budget Management at the Denpasar KPKNL for the 2017-2021 period and find out the efforts of the Denpasar KPKNL in achieving effective and efficient budget management. The result of this activity is that the Denpasar KPKNL has effectively realized the budget to achieve agency goals and is efficient in optimizing the budget for the implementation of activities. The Denpasar KPKNL carries out a quarterly action plan strategy and section coordination to seek effective and efficient budgeting records. The activity concludes that the Denpasar KPKNL has effective performance and efficient budget management.